An Analysis of Reading Questions in “English for Senior High School Grade XII” Textbook Published by Masmedia - Niken Sakinah; Nora Fudhla (Journal of English Language Teaching, 2023)
This research aims to analyze LOTS, MOTS, and HOTS reading questions in different texts from the English for Senior High School Grade XII textbook. In Barrett's Taxonomy, Lower-Order Thinking Skill involve literal comprehension and reorganization, Middle-Order Thinking Skill involve inferential comprehension, and Higher-Order Thinking Skill involve evaluation and appreciation. By using a descriptive quantitative research design, the researcher used a checklist table with Barrett's Taxonomy indicators to collect and analyze the data. The results showed that only four cognitive levels were found; literal comprehension, reorganization, inferential comprehension, and evaluation. Meanwhile, appreciation was not found in reading questions in any kind of text. A total of 78 reading questions were found in discussion text, review text, and song lyrics, in the textbook. It was found that the percentage of LOTS is 43.5% (24.3% in discussion text, 16.6% in review text, and 2.6% in song lyrics), MOTS is 48.7% (6.4% in discussion text, 16.7% in review text, and 25.6% in song lyrics), and HOTS is 7.7% (3.8% in discussion text, 1.3% in review text, and 2.6% in song lyrics). Besides, the proportion of the LOTS, MOTS, and HOTS reading questions found is almost sufficient because the recommendation of LOTS should be 40%, MOTS should be 40%, and HOTS should be 20%. Moreover, the highest percentage of HOTS reading questions was found in discussion text followed by song lyrics and review text. Therefore, it can be concluded that the textbook is sufficient for LOTS and MOTS proportions, but insufficient for HOTS proportions.